Perception on Usability and Risk of E-Business Platform for Women Managed Small and Medium Weaving Enterprises - I Gusti Ayu Purnamawati; I Gusti Bagus Baskara Nugraha (International Journal of Social Science and Business, 2021)
Rapid technological advances in information and communication technology have resulted in distance no longer a major problem in conducting business activities. Every individual and business actor is also carried away by the flow of having tools that can support their daily activities have been parts of the existence of technology. This study analyzes the effect of usability and risk perception in small and medium weaving enterprises (SMWE), which women manage, in using e-business, e.g., online shops, e-commerce, and marketplaces. We surveyed 43 SMWEs using questionnaires and interviews and selected the samples using the saturated sampling technique. Quantitative data was collected through a Likert scale and then analyzed using multiple linear regression. The study results show that usability positively affects the interest in using e-business in SMWEs. Meanwhile, the risk perception variable has a negative and significant direction. Usability makes it easier for individuals to understand and easy to get information in using e-business. The use of information systems can speed up work and provide flexibility in convenience. The risks faced by e-business users are transaction security and the uncertainty of the goods ordered. Perceived risk will hurt the individual’s intention to use the online store. This prediction arises based on logic if the higher risk on online transactions lacks necessary trust.